Trends in Biology Learning Innovations for Strengthening 21st Century Skills Toward Achieving the Sustainable Development Goals (SDGs) - Indah Rahmawati; Dora Dayu Rahma Turista (Postgraduate, University of Mataram, 2026)
This study analyzes publication trends in biology learning innovation linking 21st Century Skills and the Sustainable Development Goals (SDGs) using a bibliometric approach. Data sourced from Google Scholar (n = 637) were extracted using the Publish or Perish tool and converted into CSV and RIS formats., then filtered based on inclusion criteria (journal articles and book chapters; English/Indonesian), resulting in 313 final documents, with 171 documents discussing specific learning innovation (models/approach). Data were analyzed using VOSviewer for keyword co-occurrence and Excel for frequency analysis. The results show an increasing research trend in 2022–2025, with the dominant topic being technology integration, especially artificial intelligence (AI). Indonesia surpasses the UK and US in publications on this topic. The dominant learning innovations are STEM/STEAM (21%; links 27), PjBL (11%; links 19), and PBL (6%; links 16). Co-occurrence analysis links these innovations with critical thinking, creativity, problem-solving, collaboration, and digital literacy. These innovations connect to SDGs 4 and 13 (primary goals), and SDGs 6, 9, 11, and 12 (subsidiary goals), confirming their relevance in strengthening 21st-century skills and sustainable development goals. Their effective implementation depends on teacher preparedness, curriculum adaptability, and institutional support, requiring research across educational contexts.